Implementing scalable face-to-face and digital interventions among forcibly displaced persons from Ukraine in Europe: protocol of The U-RISE Project - Karl J. Weinreich; Iryna Frankova; Natalie Maksymets; Corrado Barbui; Vitalii Klymchuk; Trudy Mooren; Emilia Olechno; Marianna Purgato; Marit Sijbrandij; Anke B. Witteveen; Els van der Ven (European Journal of Psychotraumatology)
Background: The full-scale Russian invasion of Ukraine on 24 February 2022 has led to millions of forcibly displaced persons (FDPs) within Ukraine and other European countries. Due to war-related exposure and displacement adversities, this group is at significant risk of developing depression, anxiety, post-traumatic stress disorder, and other mental health problems. Systemic barriers, including insufficiently equipped mental health systems and language barriers, prevent FDPs from receiving adequate mental health and psychosocial support (MHPSS). Scalable interventions delivered in person by non-specialist helpers, or digitally, provide opportunities to scale up the MHPSS response.Objectives: This paper aims to provide an overview of the ‘Ukraine’s displaced people in the EU: Reach out, Implement, Scale-up and Evaluate interventions promoting mental wellbeing’ (U-RISE) project. U-RISE aims to improve the mental wellbeing of FDPs from Ukraine by establishing a network of Ukrainian mental health professionals, building sustainable capacity for provision and supporting implementation of scalable face-to-face and digital mental health interventions adapted to the specific needs of this population.Method: We build capacity for and implement scalable face-to-face interventions, including Problem Management Plus, Self Help Plus, and Multi-family Approach, for FDPs from Ukraine in Poland, Slovakia and Romania. Digital interventions, including the Doing What Matters in Times of Stress digital guide and a Telegram-based chatbot ‘Friend’ using principles of Psychological First Aid, are being implemented in Europe and Ukraine. To monitor the population’s mental wellbeing and impact of the interventions, qualitative needs assessments among mental health providers and FDPs, and quantitative assessments pre- and post-intervention are collected.Conclusion: We provide a framework for the rapid implementation of face-to-face and digital interventions in countries that need to scale up their MHPSS in response to humanitarian or complex emergency crises.